Correlation between blood pressure control status and cognitive impairment in older adults: A national cross-sectional study. - Junxiu Yao; Shengshu Wang; Meiling Li; Baomei Song; Cong Lan; Jianjun Jia; Yongjian Yang (PLoS ONE)
Hypertension is closely related to cognitive impairment; however, the correlation between blood pressure control and cognitive impairment in the hypertensive population is unclear. We aimed to explore the relationship between blood pressure control and cognitive impairment in older adults with hypertension. Using the cross-sectional data from the 2018 Chinese Longitudinal Healthy Longevity Survey, 5,860 people with self-reported history of hypertension were divided into the hypotension, intermediate blood pressure, and hypertension groups. Cognitive impairment was defined as a score of < 18 on the Chinese version of the Mini-Mental State Examination. Demographics of the population were also collected. Bivariate Logistic regression analysis and restricted cubic spline (RCS) model were used to analyze the relationship between blood pressure control and cognitive impairment. After adjusting for confounding factors, binary logistic regression analysis showed that the intermediate group was significantly associated with an increased risk of cognitive impairment than the hypotension group, whereas the hypertension group was significantly correlated with a reduced risk of cognitive impairment. No significant correlation was found between blood pressure control and cognitive impairment in patients aged <80 years, with hearing impairment, or with cerebrovascular diseases, whether in the hypotension or hypertension groups. There was a significant correlation between hypotension and cognitive impairment, and no correlation between hypertension and cognitive impairment in people aged ≥ 80 years, Han ethnicity and those who used antihypertensive drugs. Furthermore, RCS model analysis showed that there was a non-linear relationship between systolic blood pressure and cognitive impairment in individuals aged ≥ 80 years and those using antihypertensive drugs. There was a linear relationship between diastolic blood pressure and cognitive impairment. Blood pressure control in the hypertensive group was significantly associated with a lower risk of cognitive impairment.